TANTANGAN PENERAPAN ANALISIS DAMPAK DALAM LEGISLASI INDONESIA - Nalle, Victor Imanuel W.; Kristina, Jennis (Faculty of Law, Parahyangan Catholic University, 2020)
Quality of legislation, undoubtedly, is influenced by the preliminary legal research conducted. But there is more, as a number of members of the Organization for Economic Co-operation and Development (OECD) in this context also utilizes impact assessment studies to guarantee good legislations. The question discussed here is to whether impact assessment study should also be used by the Indonesian parliament. By looking at countries which already implement this approach, it is found that such impact assessment study can only be performed if experts are readily available. In any case, the author recommends that the government adopt this approach in the making of statutes.